Characterization of the novel KIR2DL4*037 allele identified in a Chinese Hani individual. (9th May 2019) - Su, Pincan; Yang, Tonghua; Ma, Haili; Zhang, Guobin; Deng, Zhi‐Hui
Abstract : The novel KIR2DL4*037 allele differs from the closest allele KIR2DL4*00501 by a single missense mutation.